1D vs. 2D shape selectivity in the crystallization-driven self-assembly of polylactide block copolymers. Issue 6 (13th April 2017) - Inam, Maria; Cambridge, Graeme; Pitto-Barry, Anaïs; Laker, Zachary P. L.; Wilson, Neil R.; Mathers, Robert T.; Dove, Andrew P.; O'Reilly, Rachel K.
Abstract : Assemblies of polylactide-based amphiphiles in alcohols are shown to give unprecedented shape selectivity based on unimer solubility, leading to the formation of large uniform 2D diamond-shaped platelets, up to several microns in size. Abstract : 2D materials such as graphene, LAPONITE® clays or molybdenum disulfide nanosheets are of extremely high interest to the materials community as a result of their high surface area and controllable surface properties. While several methods to access 2D inorganic materials are known, the investigation of 2D organic nanomaterials is less well developed on account of the lack of ready synthetic accessibility. Crystallization-driven self-assembly (CDSA) has become a powerful method to access a wide range of complex but precisely-defined nanostructures. The preparation of 2D structures, however, particularly those aimed towards biomedical applications, is limited, with few offering biocompatible and biodegradable characteristics as well as control over self-assembly in two dimensions. Herein, in contrast to conventional self-assembly rules, we show that the solubility of polylactide (PLLA)-based amphiphiles in alcohols results in unprecedented shape selectivity based on unimer solubility. We use log  P oct analysis to drive solvent selection for the formation of large uniform 2D diamond-shaped platelets, up to several microns in size, using long, soluble coronal blocks. By contrast, less soluble PLLA-containing block copolymers yield cylindrical micelles and mixed morphologies. The methods developed in this work provide a simple and consistently reproducible protocol for the preparation of well-defined 2D organic nanomaterials, whose size and morphology are expected to facilitate potential applications in drug delivery, tissue engineering and in nanocomposites.